2010
DOI: 10.3960/jslrt.50.59
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Perforation Caused by Epstein-Barr Virus-Associated B Cell Lymphoma in a Patient with Angioimmunoblastic T-Cell Lymphoma

Abstract: On rare occasions, secondary Epstein-Barr virus (EBV)-associated B cell lymphoma can develop in a patient with angioimmunoblastic T-cell lymphoma (AITL). We report a case of a 66-year-old Japanese woman who developed diffuse large B-cell lymphoma (DLBCL) in her small intestine after chemotherapy for AITL. She was found to have panperitonitis due to perforation of the small intestine. Partial ileectomy specimen showed DLBCL cells infiltrating into the intestinal wall. In situ hybridization for EBV-encoded RNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Whether or not specific mechanism involved in the sequential development of EBV-associated B-cell lymphoma in AITL derived from non-EBV-infected cells should be investigated further. Seven cases have been reported that the secondary B-cell lymphoma develop in extranodal organs, including skin, bone marrow, duodenal bulbous, lung, ileum and soft tissue [4,7-12], and only two cases as well as ours presented skin involvement by secondary B-cell lymphoma [4,8]. The present case is the first report on cutaneous sequential development of EBV-associated DLBCL from AITL in Chinese patients.…”
Section: Case Presentationmentioning
confidence: 51%
“…Whether or not specific mechanism involved in the sequential development of EBV-associated B-cell lymphoma in AITL derived from non-EBV-infected cells should be investigated further. Seven cases have been reported that the secondary B-cell lymphoma develop in extranodal organs, including skin, bone marrow, duodenal bulbous, lung, ileum and soft tissue [4,7-12], and only two cases as well as ours presented skin involvement by secondary B-cell lymphoma [4,8]. The present case is the first report on cutaneous sequential development of EBV-associated DLBCL from AITL in Chinese patients.…”
Section: Case Presentationmentioning
confidence: 51%
“…To our knowledge, only 21 cases of AITL with histologic progression to EBV-associated B cell lymphoma, involving nodal (13/21) and extranodal (8/21) sites, have been described in English literature [1422, 24]. Reported extranodal sites of involvement include skin (three cases) [18–20], bone marrow (two cases) [14, 15], ileum (one case) [21], soft tissue (one case)[24], and lung (one case) [22]. The present case is the first report of CNS involvement as extranodal manifestation of EBV-associated B cell lymphoma following a diagnosis of AITL.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even though the neoplastic T cells are EBV-negative, high-grade histologic progression, when occurring in rare occasions, is usually to a B cell lymphoma that is usually EBV-positive [14]. Reported sites of involvement include lymph node [14–17], skin [18–20], bone marrow [14, 15], small intestine [21], and lung [22]. To our knowledge, central nervous system (CNS) involvement by an EBV-positive B cell lymphoma following a diagnosis of AITL has not been previously documented in literature.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility is supported by previous reports, which documented expansion of EBV-negative B-cell clones in AITL 3,5,6 as well as development of EBV-positive B-cell lymphomas in some cases in which the original AILT lacked detectable EBV-positive cells. 1,39 …”
Section: Discussionmentioning
confidence: 99%